ANALISIS FAKTOR YANG MEMPENGARUHI PRODUKSI USAHA PERIKANAN KOLAM DI KECAMATAN XIII KOTO KAMPAR KABUPATEN KAMPAR - Lestari Ayu Elsa; Eriyati Eriyati; Aqualdo Nobel (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2020)
This study aims to determine what factors affect the production of pond fisheries in XIII Koto Kampar District, Kampar Regency. The population of this study is the total number of pond fishery farming in the XIII Koto Kampar District is 562 pond fishery households, then based on the Slovin formula with a level of 10%, the total sample size is 85 respondents. The analytical method used is descriptive quantitative using multiple linear regression analysis. Based on the results of the study, it is known that the area of the pond, initial capital, labor and production costs affect the production of the pond fishery business simultaneously or collectively. However, partially the production of pond fishery business is influenced by the size of the pond, initial capital, labor and production costs in the XIII Koto Kampar District, Kampar Regency. Furthermore, capital is the dominant factor affecting the production of pond fisheries in XIII Koto Kampar District, Kampar Regency. This can be seen from the initial capital beta coefficient which is greater than other variables so that changes in capital increase production more. Keywords: Fishery Business, Production, Pool Area, Initial Capital, Labor and Production Costs